Management of acute cholecystitis in elderly patients: A propensity score-matched analysis of surgical vs. medical treatment. Issue 12 (December 2021) - Rosa, Fausto; Covino, Marcello; Cozza, Valerio; Fransvea, Pietro; Quero, Giuseppe; Fiorillo, Claudio; Simeoni, Benedetta; Sganga, Gabriele; Gasbarrini, Antonio; Franceschi, Francesco; Alfieri, Sergio
Abstract: Background: Acute cholecystitis (AC) is a life-threatening emergency in elderly patients. Aims: To compare the commonly used management strategies for elderly patients with AC as well as resulting morbidity, mortality and length of hospital stay (LOS). Methods: All patients ≥ 65 years admitted to our emergency department for AC between January 1st, 2014 and December 31st, 2018 were included in the study. We compared patients that received medical treatment to patients who received operative procedures. In order to correct for baseline covariates and factors associated to clinical management, we used a 1:1 propensity score matching (PSM) analysis. The primary outcome was the overall in-hospital mortality. Secondary outcomes included occurrence of major complications and LOS. Results: A total of 1075 patients were enrolled: 483 patients received a medical treatment and 592 patients underwent interventional procedures. After PSM, 770 patients (385 for each treatment group) were included in the analysis. The analysis revealed that both mortality and cumulative major complications were similar in medical and interventional group. We found that among comorbidities, Charlson comorbidity index and congestive heart failure were significantly higher in the medical treatment group (5 [4-6] vs. 4 [3-6] and 11.7% vs. 4.7%, respectively; p <0.001). LOS was slightly lower in the medical treatment group (7.0 days [4.9–11.1] vs. 7.9 [4.9–13.5]; p = 0.046). Conclusion: Medical management outcomes for AC in elderly patients were similar to operative treatments in terms of mortality and cumulative major complications. A conservative approach should always be considered.